Growth of CrSi2 Nanostructures Using CrCl2 Powder on Si Substrates - Li, Wen; Erchao, Meng; Matsushita, Tomoji; Oda, Shingo; Ishikawa, Daisuke; Nakane, Kaito; Tatsuoka, Hirokazu (Makara Journal of Technology, 2013)
Chromium disilicide (CrSi2) nanostructures were grown by the exposure of Si (111) substrates to CrCl2 vapor in an argon gas flow at atmospheric pressure without using any metal catalyst. Dependence of the growth condition on the structural property was investigated. Hexagonal-shaped CrSi2 microrods were grown at 750 °C with 0.05 g of CrCl2. As the quantity of CrCl2 increased to 0.1 g, the bundle of CrSi2 nanowires with microrods and web-liked CrSi2 nanostructure with turning angles were grown at 750 °C and 700 °C, respectively. The preliminary discussion on the growth mechanism of CrSi2 micro- and nanostructures was carried out.